DENPASAR SEBAGAI KOTA KREATIF BERWAWASAN BUDAYA : ANTARA IDEALITAS DAN REALITAS - Wira Dharma, A. A. Gede Ksatriya (Humanis, 2016)
Determination of Denpasar as a creative city cultural insight is one of the Denpasar government efforts to follow the Indonesian government programs that have been launched in Indonesia Creative activities in 2009 as a blueprint for the implementation of the Economic Development Culture-Based Creative Featured 2009-2025. Creative Economy is a manifestation of efforts to achieve sustainable development through creativity and competitive economic climate and have a renewable resource. The problem studied in this research are: (1) Why Denpasar defined as Creative City Cultural Insight? (2) How is the public perception regarding the determination of Denpasar as a Creative City Cultural Insight? (3) How does the empirical reality in the lives of people in Denpasar as a Creative City Cultural Insight? This reseach is the emphasis on qualitative methods, the analysis focuses on the "Descriptive interpretive". The results of this study revealed that: Denpasar reasons set as insightful creative city of culture, because Denpasar is one tourism destination in Bali and has a diverse culture can enhance creativity and community economy. Public perception provides a mixed response, but more feel disadvantaged communities after such determination. Empirical reality in the field of economics that is more increased Denpasar community economy, the social sector increased infrastructure and municipal services, and in the fields of culture, preserving culture in the city of Denpasar through various activities undertaken by the Department of Culture and the artists.
Keywords: Creative City, Perception, Cultural Insights.